2005
DOI: 10.1001/archinte.165.11.1286
|View full text |Cite
|
Sign up to set email alerts
|

Restless Legs Syndrome Prevalence and Impact

Abstract: Clinically significant RLS is common (prevalence, 2.7%), is underdiagnosed, and significantly affects sleep and quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

48
718
15
58

Year Published

2008
2008
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,112 publications
(839 citation statements)
references
References 17 publications
48
718
15
58
Order By: Relevance
“…The prevalence of RLS is estimated to be about 10% and increases with age, smoking, anemia, obesity and renal failure (25). In a recent large scale population based study, a 5% prevalence of weekly symptoms and 2.7% prevalence of at least twice weekly symptoms have been reported (26). In our study, RLS was reported in 16.3% of the wrestlers and in 4.5% of the control subjects.…”
Section: Discussionsupporting
confidence: 58%
“…The prevalence of RLS is estimated to be about 10% and increases with age, smoking, anemia, obesity and renal failure (25). In a recent large scale population based study, a 5% prevalence of weekly symptoms and 2.7% prevalence of at least twice weekly symptoms have been reported (26). In our study, RLS was reported in 16.3% of the wrestlers and in 4.5% of the control subjects.…”
Section: Discussionsupporting
confidence: 58%
“…From a clinical point of view, both conditions are characterized for being chronic diseases with periodic exacerbations, involving more women and having an important impact on quality of life and quality of sleep 3,[25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…RLS remains largely undiagnosed and underestimated. Nevertheless most patients do experience serious clinical consequences with a significant impact on sleep and life quality [1,2,5].…”
Section: Introductionmentioning
confidence: 99%